Pengaruh Kecerdasan Emosional dan Beban Kerja Serta Komunikasi terhadap Kinerja pada Rumah Sakit Dirgahayu Samarinda - Agustina Maulani; Sukisno S. Riadi; Siti Maria (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this research was to verify the effect of emotional intelligence and workload and communication toward  performance of Dirgahayu Hospital Samarinda. To collected the data in this research, researcher used purposive sampling method. The sample which used in this research was 80 respondents with the criteria of nurse who has been worked in Dirgahayu Hospital Samarinda at last two years. This research used multiple linier regression analysis with  SPSS as an instrument to calculate the data. The result showed that there was a positive effect and significant between emotional intelligence toward nurse performance. And there was also a positive effect and significant between workload toward nurse performance. And positive effect and significant between communication toward nurse performance.